EXISTENCE OF NOTARY AUTHORIZATION DUE TO MAKING AUTHORIZED LOADING RIGHTS REVIEWED FROM LAW NUMBER 2 OF 2014 ABOUT NOTARY POSITION - Arpangi Arpangi; Satria Ardi Yana (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2020)
In its development in terms of making the Deed of Granting Mortgage or APHT the debtor can not be present which is then represented by his representative, the consequences of the debtor's representative then the APHT must be made with SKMHT or Power of Attorney Imposing Mortgage Rights. The SKMHT is made by a notary public. But in its development based on Article 96 PMNA / Per.Kaban No. 3 of 1997 as amended by Regulation No. 8 of 2012 requires that the deed is made in accordance with the form or form made by the BPN or the Land Agency, even though it is clear that it has contradicted the provisions related to the deed according to Article 15 paragraph (1) of Law Number 2 of 2014 is not quite right, this is because The notary is authorized to make an authentic deed, not to make a letter, or fill in blanks, such as SKMHT where the manuscript is made by BPN. So it is clear that the current SKMHT has contradicted the provisions referred to in Article 15 paragraph (1) of Law Number 2 of 2014. The type of research in this writing is sociological juridical. The data collection techniques in scientific research is to use literature study techniques and direct interview studies with informants in collecting and compiling the data needed. This research is a descriptive qualitative analytical research which is a study with data analysis techniques in the form of describing, analyzing, explaining, and analyzing a legal problem that occurs.Keywords: Authentic Deed, Existence, Notary, Power of Attorney, Letter of Mortgage Right